Perkembangan Pementasan Tari Maena Dalam Pesta Pernikahan Di Desa Duria Kecamatan Lolofitu Moi Kabupaten Nias Barat Tahun 1998-2024 - Halawa, Wiarsen Wiarsen; Rusdi, Rusdi (Jurusan Sejarah FIS UNP, 2025)
Maena Dance is a traditional dance of the Nias people which means togetherness, unity and joy, often performed at weddings. This research aims to analyze the development of Maena Dance performances at wedding parties in Duria Village in 1998–2024, as well as efforts to preserve it. This research uses historical methods with heuristic stages, source criticism, interpretation, and historiography. Data was collected through literature study, observation, and direct interviews with local communities. The research results show that Maena Dance has experienced significant changes in aspects of dancers, music, costumes and poetry. The intensity of this dance performance is influenced by social, economic and cultural factors of the Duria Village community. Economic limitations are the main obstacle in its implementation, especially among people with low incomes. However, revitalization efforts, such as training through art studios and government support, have succeeded in keeping this tradition alive. The conclusion of this research is that the Maena Dance remains an important symbol in wedding parties in Duria Village, reflecting the community's adaptation to changing times while maintaining core cultural values. This research provides insight into the importance of preserving local culture as part of community identity.